2013
DOI: 10.1007/s00344-012-9312-6
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence for the Role of Ethylene in Strawberry Fruit Ripening

Abstract: It has been suggested that the phytohormone ethylene plays a role in strawberry fruit ripening, and new genetic evidence for the role of this hormone in strawberry ripening is provided in this study. The combined analysis of ethylene production and transcripts of the ethylene biosynthesis-related gene FaSAMS1 and the signaling gene FaCTR1 in 'Camarosa' strawberry (Fragaria ananassa) fruit showed that an increase in ethylene production was concomitant with a rise in transcripts of the two genes during fruit red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 54 publications
1
40
1
Order By: Relevance
“…Non-climacteric fruits are able to synthesize ethylene; therefore, the involvement of this hormone in physiological and molecular events has been reported during strawberry development and ripening (Trainotti et al, 2005;Villarreal et al, 2010;Merchante et al, 2013;Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Non-climacteric fruits are able to synthesize ethylene; therefore, the involvement of this hormone in physiological and molecular events has been reported during strawberry development and ripening (Trainotti et al, 2005;Villarreal et al, 2010;Merchante et al, 2013;Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although SAM synthetase committed the first step in ethylene biosynthesis is proved to plays a role in strawberry fruit ripening (Sun et al, 2013), the biochemical properties of FaSAMS1 protein remain unclear. In the present study, it is confirmed that FaSAMS1had high enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, much progress has been made in understanding the molecular mechanisms of ethylene in the regulation of climacteric fruit ripening using the model plant tomato (Klee and Giovannoni, 2011). Notably, in recent years, ethylene is also involved in the regulation of non-climacteric fruit ripening using the model plant strawberry (Sun et al, 2013), demonstrating that downregulation of the ethylene biosynthesis-related gene FaSAMS1inhibits ripening. However, the biochemical nature of the FaSAMS1 protein remains yet unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations